From Protest to Political Transition: International Responses to Bangladesh's 2024 Movement in the Context of Emergency Constitutional Law - Md Ali Ashraf; Muhammad Mahmudur Rahman; Md. Basirulla (CV. Pustaka Parawali, 2025)
This paper examines how other countries reacted to the July 2024 student movement in Bangladesh through the prism of constitutional crisis and emergency rule. The demonstrations that began over the reinstatement of the civil service quota system quickly escalated into a nationwide struggle against the constitutional order, marked by rampant violations of constitutionally guaranteed rights, including the right to life and personal liberty, freedom of assembly and expression, and the right against arbitrary arrest. The state's response, manifested in the overuse of force, mass detentions, and long-term internet bans, in fact, precipitated a de facto constitutional crisis without a declaration of a state of emergency. This study will employ a qualitative research design, using documentary and thematic content analyses of official statements, human rights reports, international media coverage, and policy briefs published between July 2024 and February 2025. The results show a clear split in international reactions: Western democracies and international human rights institutions interpreted the crisis as a problem of constitutionality, the rule of law, and international human rights commitments, whereas regional powers viewed it as a problem of political stability, sovereignty, and non-intervention. The article also suggests that continued international pressure, together with mobilization within the country, contributed greatly to undermining the legitimacy of the existing government and to the formation of the interim government operating under the conditions of constitutional necessity. The place of international responses within the context of constitutional emergency and international human rights law, therefore, allows the study to contribute to comparative constitutionalism studies on how international actors affect constitutional failure and post-crisis state politics.